Turkic lexicography: the structured-content character of bilingual translations dictionaries - Lyazat Meirambekova, Karlygash Sarekenova, Kusni Taimullina, Gulgaisha Sagidolda, Gulimzhan Zhylkybay, (Opción, 2020)
The article is devoted to the analysis of the history of the formation and development of Turkic lexicography from the XI century, to the consideration of the systematic, structural problems of the Turkic languages dictionaries, including the explanatory and bilingual dictionaries in Kazakh lexicography. As a result, the foundations of the history of general lexicography have been established and the sources of the history of the scientific study of lexicography in the Turkic languages have been discovered. In conclusion, the history of Turkic lexicography beginning with the XI century can be divided into four stages with methodological, practical and scientific theoretically distinctive features.